2021
DOI: 10.1152/jn.00620.2020
|View full text |Cite
|
Sign up to set email alerts
|

Envelope following responses predict speech-in-noise performance in normal-hearing listeners

Abstract: Permanent threshold elevation after noise exposure or aging is caused by loss of sensory cells; however, animal studies show that hair cell loss is often preceded by degeneration of the synapses between sensory cells and auditory nerve fibers. Silencing these neurons is likely to degrade auditory processing and may contribute to difficulties understanding speech in noisy backgrounds. Reduction of suprathreshold ABR amplitudes can be used to quantify synaptopathy in inbred mice. However, ABR amplitudes are high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 47 publications
1
42
0
1
Order By: Relevance
“…In recent work from our lab, the EFR to a rectangular stimulus was found to be a good predictor of HP speech reception in SWN in normal hearing listeners (Mepani et al, 2021). This stimulus was not only designed to boost synchrony to the stimulus envelope of midbrain nuclei to the stimulus envelope, but also to enhance differences based on cochlear synaptopathy, while being relatively insensitive to HF hearing loss.…”
Section: Introductionmentioning
confidence: 89%
“…In recent work from our lab, the EFR to a rectangular stimulus was found to be a good predictor of HP speech reception in SWN in normal hearing listeners (Mepani et al, 2021). This stimulus was not only designed to boost synchrony to the stimulus envelope of midbrain nuclei to the stimulus envelope, but also to enhance differences based on cochlear synaptopathy, while being relatively insensitive to HF hearing loss.…”
Section: Introductionmentioning
confidence: 89%
“…Three experiments found that performance on a modified, difficult version of the QuickSIN correlated with ABR measures [one experiment in Grant et al (2020); one in Mepani et al (2020)] or EFRs [one in Mepani et al (2021)].…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…The three studies reporting significant relationships between sentence identification performance and CS proxies also employed stimuli to elicit electrophysiological responses that may be better suited to identify CS-related AN degeneration than those utilized by many other human studies [see Table 2 in Supplemental Digital Content 1, http://links.lww.com/EANDH/A935; Bharadwaj et al 2019; Vasilkov et al 2021; see discussions in Grant et al (2020); Mepani et al (2020); and Mepani et al (2021) for further details]. These findings thus highlight the importance of developing both electrophysiological proxies of CS and speech perception tasks in difficult listening conditions that are sensitive to CS.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Garrett et al (2020) observed a strong correlation between a rectangularly amplitude modulated (RAM) EFR magnitude and speech intelligibility of young and older normal-hearing and hearing impaired subjects. In this regard, Mepani et al (2021) found a weak but significant correlation between RAM-EFR magnitude and word recognition scores of normal-hearing listeners. However, other studies did not confirm these findings, e.g.…”
Section: Introductionmentioning
confidence: 85%